Evolution of drug therapy in patients with resectable gastric and esophageal‑gastric junction cancer - M. V. Sedova; M. A. Batov; V. S. Tretyak; A. A. Kolomeytseva; V. M. Khomyakov; N. N. Volchenko; A. A. Fedenko; A. D. Kaprin (Исследования и практика в медицине)
Gastric cancer (GC) is the fifth most common malignant neoplasm in the world among all malignant tumors. Currently, the “gold” standard of treatment for patients with non‑metastatic cancer of the stomach and esophageal–gastric junction is surgical treatment, which is complemented by perioperative chemotherapy according to the FLOT scheme, which includes four courses of therapy before surgery and four after. However, according to statistics, less than half of patients complete all adjuvant courses of FLOT chemotherapy due to the high toxicity of the regimen and a decrease in the functional status of patients in the postoperative period. In this regard, studies are being conducted to study the tolerability of total neoadjuvant chemotherapy, when all courses are held at the preoperative stage in order to carry out all stages of treatment in full. International studies have shown the results of the use of targeted (ramucirumab, trastuzumab, pertuzumab), immune drugs (pembrolizumab, nivolumab, ipilimumab), S‑1 in combination with chemotherapy as part of the combined treatment of gastric and esophageal‑ gastric junction cancer. The emergence of new therapeutic agents previously studied in metastatic GC may change approaches to the treatment of localized and locally advanced GC.The review presents the features of perioperative therapy regimens in patients with resectable gastric and esophageal‑ gastric junction cancer in order to reduce the frequency of local and long‑term relapses and improve further prognosis.